Whole genome sequence data of Trichoderma yunnanense strain TM10, a plant growth-promoting fungus and biocontrol agentNCBI - Dedat Prismantoro; Kah-Ooi Chua; Kelly Wan-Ee Teo; Rosamond Chan; Thomas Argyarich Jefferson; Nurul Shamsinah Mohd Suhaimi; Muhamad Shakirin Mispan; Mia Miranti; Febri Doni (Data in Brief)
Trichoderma yunnanense strain TM10 was isolated from rhizosphere soil of rice plants cultivated under system of rice intensification (SRI) practises in West Java, Indonesia. It exhibits significant potential as a plant growth promoter and biocontrol agent in rice plants. Although this strain has shown promise in promoting plant growth and suppressing phytopathogens under in vitro and in planta conditions, there is still a lack of genomic data to elucidate the molecular mechanisms underlying its plant growth-promoting and biocontrol capabilities. This study reports the whole genome sequence of T. yunnanense strain TM10. The genome of the fungus was sequenced using the MGI DNBSEQ-G400 high-throughput sequencing platform. The assembled genome of T. yunnanense strain TM10 was approximately 36 Mbp in length, comprising 385 contigs with a GC content of 48 % and a sequencing coverage of 43.8×. This genomic data provides a foundation for harnessing the plant growth-promoting and biocontrol potential of this strain. The complete genome sequence has been deposited at the National Center for Biotechnology Information (NCBI) under Bioproject accession number PRJNA1181959, BioSample ID SAMN44575400, and genome accession number JBIYZQ000000000. These data are valuable for further research into the biotechnological potential of this strain and for exploring the molecular mechanisms underlying its plant growth-promoting and biocontrol activities.